2016
DOI: 10.1021/acscatal.6b00668
|View full text |Cite
|
Sign up to set email alerts
|

Electrochemical Behavior of Electrodeposited Nanoporous Pt Catalysts for the Oxygen Reduction Reaction

Abstract: Nanoporous Pt based nanoparticles (NP’s) are promising fuel cell catalysts due to their high surface area and increased electrocatalytic activity toward the ORR. In this work a direct double-pulse electrodeposition procedure at room temperature is applied to obtain dendritic Pt structures (89 nm diameter) with a high level of porosity (ca. 25%) and nanopores of 2 nm protruding until the center of the NP’s. The particle morphology is characterized using aberration-corrected high angle annular dark field scannin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

4
62
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 57 publications
(70 citation statements)
references
References 49 publications
4
62
0
Order By: Relevance
“…The dissolution of the less noble component is coupled with diffusion and aggregation of the more noble metal element at the solid/liquid interface: the overall process leaves behind a porous metal structure (a metal “sponge”) that can be enriched or mainly composed of the nobler element . Nanoporous metals prepared via selective dealloying of solid solutions possess a three‐dimensional (3D) structure of randomly interpenetrating ligaments/pores with sizes between a few nm to several tens of μm; these structural features can be precisely tuned by varying the preparation conditions (such as alloy composition, dealloying time, temperature, and electrochemical parameters) or by subsequent a thermal coarsening step …”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The dissolution of the less noble component is coupled with diffusion and aggregation of the more noble metal element at the solid/liquid interface: the overall process leaves behind a porous metal structure (a metal “sponge”) that can be enriched or mainly composed of the nobler element . Nanoporous metals prepared via selective dealloying of solid solutions possess a three‐dimensional (3D) structure of randomly interpenetrating ligaments/pores with sizes between a few nm to several tens of μm; these structural features can be precisely tuned by varying the preparation conditions (such as alloy composition, dealloying time, temperature, and electrochemical parameters) or by subsequent a thermal coarsening step …”
Section: Introductionmentioning
confidence: 99%
“…[24] Nanoporous metals prepared via selective dealloying of solid solutions possess a three-dimensional (3D) structure of randomly interpenetrating ligaments/pores with sizes between a few nm to several tens of mm; these structural features can be precisely tuned by varying the preparation conditions (such as alloy composition, dealloying time, temperature, and electrochemical parameters) or by subsequent a thermal coarsening step. [18,[25][26][27][28][29] In spite of the large application in heterogeneous catalysis, there is however still a comparably low number of studies on nanoporous metal co-catalysts for photocatalytic applications. Nguyen et al have reported on porous Au, [30] AuPt, [31] or PtPd [32] nanoparticles produced on TiO 2 nanotubes (NTs) by chemical dealloying of dewetted-alloyed nanoparticles.…”
Section: Introductionmentioning
confidence: 99%
“…The control of the electrode structure is not easy, as the dispersion medium governs the ink's properties like viscosity, dispersion and aggregation size of the catalyst/ionomer particles, rate of solidification and ultimately the physical and mass transport properties of the catalyst layer. Researchers have come up with various new techniques such as plasma sputtering, ion beam bombardment, electrodeposition, electrospray, inkjet printing etc., for increasing the fuel cell performance and durability. Some of the methods, even though effective, are either too expensive to prepare in large scale or physically not possible to scale up.…”
Section: Introductionmentioning
confidence: 99%
“…It was reported 9,10 that the method of preparation, the microstructure, particle size and shape are the main factors inuencing the ORR activity of Pt-based catalysts. One of the most widely used methods is electrodeposition, [11][12][13][14][15][16] particularly potentiostatic deposition, 13,14 which has been found to be an increasingly attractive route for the preparation of nanostructured catalysts because of its ease of operation, exibility and high purity. In addition, the electrodeposition technique can be used to prepare the catalyst layer directly on the substrate in a single step with uniform particle distribution and selected particle sizes.…”
Section: Introductionmentioning
confidence: 99%